Creativity and Working Memory in Gifted Students With and Without Characteristics of Attention Deficit Hyperactive Disorder: Lifting the Mask. (October 2013) - Fugate, C. Matthew; Zentall, Sydney S.; Gentry, Marcia
There have been some behavioral indicators and some types of task performance that suggest greater creativity in students with attention deficit hyperactive disorder (ADHD). This evidence would appear counterintuitive given that lower working memory (i.e., holding information in mind for novel recombinations) has often been documented in students with ADHD. Thus, the purpose of this study was to assess working memory and creativity in two groups of gifted students (i.e., with characteristics of ADHD, n = 17, and without ADHD characteristics, n = 20), who were equivalent in fluid intelligence. Significant differences were found indicating that gifted students with ADHD characteristics had not only poorer working memory but also significantly greater creativity than those gifted students without these characteristics. These results were discussed in terms of creative potential, which could serve as an identifier and as a pathway to instruction.